The leap of your life how to take decisive action in the face of fear, redefine risk, and be happy even when you fail - Baker, Tommy (John Wiley & Sons, Incorporated, 2019)
There's a bold decision in your life you've been waiting to make, and every day passing by is a reminder of what hasn't happened. Conveniently tucked in a box labeled 'someday, ' the fear of the unknown has taken a grip on your life and put your dreams on hold. Until now. Whether your leap is quitting the soul sucking job and starting your own business, taking a bold chance on love or finally going all in on your dreams, The Leap of Your Life is the ticket to get you there. All while having the time of your life and ensuring you don't wake up years down the line with a sinking feeling of regret. Author and high-performance coach Tommy Baker has helped thousands of everyday people identify and take their leap, step into courage and create a life they can't wait to wake up for. After interviewing 250+ of the world's most powerful entrepreneurs, thought leaders, experts, spiritual teachers and athletes he discovered a common theme: They all took a leap, even if they were full of fear--and it radically transformed their experience of life. If you're ready to: Re-define risk and stop playing small Step into the boldest version of yourself Give yourself permission to take a chance Live the Hero's Journey of your life story Eradicate regret and 'what could have been' ... then look no further and order The Leap Of Your Life now!
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Management; Gestion; management; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; General; BUSINESS & ECONOMICS; Management